Influence Of Work Absenteeism, Job Satisfaction, and Organizational Culture on Organizational Commitment among Records Management Personnel in State Civil Services of South-East, Nigeria - Popoola, S.O. (MiddleBelt Journal of Library and Information Science, 2014)
This paper investigated the influence of work absenteeism, job satisfaction and organizational culture on organizational commitment of records management personnel in state civil services of south-east, Nigeria. The organizational commitment of records management personnel questionnaire with its reliability coefficient of 0.84 was the main research instrument used for the study. The questionnaire was used for the data collection on 910 randomly sampled out of a population size of 1264 records management personnel in the studied six state civil services of south-east Nigeria. All the 910 copies of the questionnaire were retrieved and found valid for analysis giving a response rate of 100 percent. The study found that organizational commitment had significant: negative correlation with work absenteeism, but positive correlations with job satisfaction and organizational culture of the respondents. Work absenteeism, job satisfaction and organizational culture had significant influence on organizational commitment of the respondents. It was also found that there was no significant difference in organizational commitment of the respondents based on their workplace. It was therefore recommended among others that the state governments and civil service administrators should urgently consider work absenteeism, job satisfaction and organizational culture when planning to improve the organizational commitment of their records management personnel.